Determinants of Employee Performance in Service-Based SMEs: The Effects of Work Discipline, Emotional Intelligence, and Communication - I Kadek Dwi Bujangga; I Gusti Ayu Imbayani; Ary Wira Andika (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Increasingly fierce business competition in the coffee shop industry requires companies to have human resources that perform optimally. Employee performance is a key factor in a company’s success because it plays a direct role in service delivery and the achievement of organizational targets. Akasa Coffee Kintamani, as one of the coffee shops in Bangli Regency, faces employee performance issues reflected in its 2024 sales realization, which averaged only 79% of the target. These issues are suspected to be influenced by work discipline, emotional intelligence, and communication that have not yet functioned optimally. This study aims to analyze the influence of work discipline, emotional intelligence, and communication on employee performance at Akasa Coffee Kintamani. This study employs a quantitative approach using a survey method. The study population and sample consist of 32 employees, selected using a saturation sampling technique. Data were collected through questionnaires, interviews, and observations, then analyzed using multiple linear regression analysis with the assistance of SPSS version 25.00. The results indicate that work discipline, emotional intelligence, and communication each have a positive and significant influence on employee performance, both partially and simultaneously. The adjusted R-squared value of 0.764 indicates that 76.4% of the variation in employee performance can be explained by these three variables, while the remainder is influenced by other variables outside the scope of this study. These findings underscore the importance of enhancing work discipline, managing emotional intelligence, and fostering effective communication as strategic efforts to improve employee performance at Akasa Coffee Kintamani.